If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7p + -6 = 4 + 8p + -6p Reorder the terms: -6 + 7p = 4 + 8p + -6p Combine like terms: 8p + -6p = 2p -6 + 7p = 4 + 2p Solving -6 + 7p = 4 + 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. -6 + 7p + -2p = 4 + 2p + -2p Combine like terms: 7p + -2p = 5p -6 + 5p = 4 + 2p + -2p Combine like terms: 2p + -2p = 0 -6 + 5p = 4 + 0 -6 + 5p = 4 Add '6' to each side of the equation. -6 + 6 + 5p = 4 + 6 Combine like terms: -6 + 6 = 0 0 + 5p = 4 + 6 5p = 4 + 6 Combine like terms: 4 + 6 = 10 5p = 10 Divide each side by '5'. p = 2 Simplifying p = 2
| 40=-2(4-x) | | 1-2-3-4-5=5 | | -1(3-2x)=17 | | 5+6(x-1)=11+5 | | 2x+2=x+15 | | 8(2x+4)-4x=20 | | 38-4x=7x-19 | | 7x+1=4x-17 | | 4x+40=13-5x | | 3(x-6)=20 | | 2x+3x+6=36 | | -3+2x+15=27 | | -52+2x=84+6x | | x^3+6x^2+6x+8=0 | | (3x+12)=5x | | 42=4x+4x-6 | | 4(3x+-5)+6=7(x-2)+6x | | 5x+7-2x+1=17 | | 3x-3+x-7+x=180 | | 4(3x+-5)+6=6x+2(3x-8) | | (4y+7)(9-y)=0 | | 3+4k-3k= | | x-(-2)=-7 | | -7y+5=8y+8 | | 4(3x+-5)+6=12x-14 | | 91-2x=9x-162 | | 5(9+-5.5)+3y=-4 | | 8x+11=6x+13 | | 2m+(-8m)= | | 5y-6x=-13 | | 4/5+1/8= | | (5n-20)=3n |